OPTIMIZING THE SUBSTITUTION LEVEL OF Lemna perpusilla IN COMMERCIAL FEED TO ENHANCE GROWTH AND FEED EFFICIENCY OF COMMON CARP (Cyprinus carpio) FINGERLINGS - Sinaga, Daniel; Matondang, Muhaini (Aurelia Journal, 2025)
Feed production costs constitute the largest expense incurred by fish farmers. Common carp (Cyprinus carpio) is highly favored by consumers due to its delicious taste and affordable price. Rearing common carp fingerlings requires high costs, particularly for feed provision. Feed supplements are needed to enhance feed quality, digestibility, and growth efficiency to reduce feed expenses. One potential feed ingredient derived from aquatic plants that can be used as a supplementary feed is Lemna perpusilla, which has high protein content and effectively improves feed quality for several freshwater fish species. This study used common carp fingerlings measuring 3–5 cm and was conducted from June to July 2023 at UPR Amphibi Batang Toru. A Completely Randomized Design (CRD) was applied with five treatments and three replications, using Lemna perpusilla supplementation at 0% (control), 10%, 20%, 30%, and 40%. The final results concluded that the most optimal and efficient Lemna perpusilla supplementation in feed was 40%, which significantly influenced the growth of common carp.